Pemanfaatan Sensor Piezoelektrik Sebagai Penghasil Sumber Energi Pada Sepatu - Maulana, Riza; , Hasyim Asy'ari, ST.MT (2016)
The utilization of conventional energy sources derived from fossil fuels decreased and getting thinner because of his willingness limited in nature and not their renewal. This prompted many studies to develop renewable energy sources, such as energy derived from geothermal energy, wind energy, wave energy. Even the smallest utilization of energy resources derived from body movement, body heat and the surrounding environment due to human activity started development and utilization of its existence. By leveraging the mobilization of human activity and body movements, the use of piezoelectric technology can be used as producing energy sources. This study contains about the utilization of piezoelectric sensor as media pressure conversion with different loads as producing energy sources. The research was done by making a small-scale prototype model which was prepared in series and in parallel where the number of piezoelectric sensors used 4 pieces in each preparation. Testing is done with a piezoelectric sensor provides a load 55kg, 60kg, and 65kg for each preparation to obtain the output voltage and current are varied. From the data generated from testing the prototype shows the preparation of parallel sensor has a maximum output power. The data obtained from the testing of piezoelectric sensors indicate when drafting in series, the output power which produced the highest of 5.8 μW with a maximum load of 65kg, while the sensor is in parallel to the preparation of the power generated reached 24.5 μW of 60kg load as an indication of the pressure exerted.